2002
DOI: 10.1176/appi.ajp.159.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Omega-3 Fatty Acid to Maintenance Medication Treatment for Recurrent Unipolar Depressive Disorder

Abstract: It is not possible to distinguish whether E-EPA augments antidepressant action in the manner of lithium or has independent antidepressant properties of its own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
349
1
16

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 514 publications
(379 citation statements)
references
References 10 publications
13
349
1
16
Order By: Relevance
“…Nevertheless, taken together, these findings appear to indicate that the lower n-3 PUFA in depressed persons reported by most of the studies may reflect, at least in part, a corresponding lower consumption of these particular fatty acids. Controlled clinical studies have shown that dietary supplementation with n-3 PUFA over a short period, led to improvements in depressive symptoms in depressed patients (Nemets et al, 2002;Peet and Horrobin, 2002;Su et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, taken together, these findings appear to indicate that the lower n-3 PUFA in depressed persons reported by most of the studies may reflect, at least in part, a corresponding lower consumption of these particular fatty acids. Controlled clinical studies have shown that dietary supplementation with n-3 PUFA over a short period, led to improvements in depressive symptoms in depressed patients (Nemets et al, 2002;Peet and Horrobin, 2002;Su et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological findings linking depression and low levels of fish intake have been reported (Hibbeln, 1998;Tanskanen et al, 2001), and biochemical research has also shown that the concentrations of each o-3 FA are significantly lower in the serum or red blood cell membranes of depressed patients than in control subjects (Edwards et al, 1998;Peet et al, 1998;Maes et al, 1999). Ethyl-EPA augmentation therapy has been reported to improve depressive symptoms in patients with major depression in randomised placebo-controlled double-blind clinical trials (Nemets et al, 2002;Peet and Horrobin, 2002) and in one clinical report (Puri et al, 2002). These trials have also reported no or a few adverse effects of the medication (e.g.…”
mentioning
confidence: 99%
“…Highly significant benefits were found with the addition of the ethyl-EPA versus placebo to standard antidepressant medication. 33 The 1999 Harvard study on 30 bipolar patients with a history of at least one relapse in the prior year, of whom all but eight were on medications, used 9.6 grams of fish oil capsules, the other half received olive oil. The omega-3 fatty acid group stayed in remission significantly longer-with a decrease in depression versus the placebo group-but had no decrease in their mania.…”
Section: Replacing Missing Nutrientsmentioning
confidence: 99%